Local community perspectives on authenticity at the ‘Street of Harmony’, George Town World Heritage Site, Penang - Bakri, Aidatul Fadzlin; Qamaruz Zaman, Nurulhusna; Samadi, Zalina (UiTM Press, 2025)
Defining authenticity is challenging, partly due to the Eurocentric bias that shapes its definition and assessment. This power dynamic, combined with the frequent neglect of intangible heritage, complicates the issue and underscores the need for a more nuanced understanding of authenticity across diverse cultural contexts. As a site recognised for its multicultural heritage and historical significance, George Town in Penang, Malaysia faces increasing pressure to balance the expectations set by UNESCO with the realities of its local communities. These factors threaten the authenticity of heritage sites by prioritising economic gain over cultural integrity, thereby diluting the sense of place that local communities associate with their heritage. Hence, this study investigates the guiding principles that support authenticity and the nuanced relationships between local and global cultural values, revealing disparities in perceptions of authenticity between local communities and authorised groups at the ‘Street of Harmony’, George Town. The site, characterised by its urban, multicultural, and postcolonial setting, was explored through observational studies and semistructured interviews. The findings highlight the pivotal role of local communities in shaping the authenticity paradigm and emphasise the importance of strengthening the sense of place to preserve cultural heritage. The research underscores the need to bridge differing interpretations of authenticity and advocates for inclusive strategies that integrate local perspectives, promote sustainable practices, and foster adaptive agreements among stakeholders. It calls for a broader, more inclusive conversation on heritage protection and management.